The Influence of Centralisation and Decentralisation Processes on Regional Tax Potential - Pechenskaya-Polishchuk, Mariya A. (Economy of Regions, 2021)
The need to stimulate economic development using policy instruments to enhance the tax potential of regions and municipalities is supported by key postulates of economic theory and successful examples of international practice. It is hypothesised that decentralising the distribution of tax revenues contributes to an increase in regional tax potential. In order to examine this problem, methods of grouping, sampling, generalisation and comparison are used. Methodological aspects of the study of tax potential at the sub-national level are presented. The scope of both centralisation and decentralisation processes affecting tax revenues in the Russian Federation for 2006-2018 is considered. The proportion of tax revenues transferred to the federal budget and collected at the regional level is investigated on the example of six Russian regional groupings. An expansion of the group of regions whose federal taxes are more than 50 % along with a 10 % increase in transfers to the federal budget led to greater centralisation. Out of the considered regions, 53 % transferred over 30 % of their tax potential to the federal level. It was revealed that regions whose tax centralisation is approximately 15-30 % have the best budget figures (debt burden of less than 30 %, budget deficit of less than 4 %, 7-9 % budget revenue growth). Continuing research aims to develop measures for increasing regional tax potential. The obtained findings can be used to substantiate and implement regulatory legal acts concerning budget and tax issues.